Tamoxifen prolongs survival and alleviates symptoms in mice with fatal X-linked myotubular myopathy - Elinam Gayi (Nature Portfolio, 2018)
X-linked myotubular myopathy (XLMTM) is a severe muscle disease with no effective treatment. Here, the authors show that tamoxifen, a drug used to treat breast cancer, rescues the pathology in a mouse model of the disease, at least in part by normalizing expression of the disease modifier proteins DNM2 and BIN1